Leveraging celebrity influence for oral cancer prevention and smokeless tobacco cessation: challenges and opportunities in India - Saravanan Sekaran; Dhanraj Ganapathy; Deepavalli Arumuganainar; Harini Arumugasamy; Vimalraj Selvaraj; Saeed Alassiri; Shahabe Saquib Abullais (Frontiers in Public Health, 2025)
India bears the highest global burden of oral cancer, with over 83,400 cases reported in 2022. The widespread use of smokeless tobacco and areca nut, particularly in rural and underserved communities, continues to drive this public health crisis. Despite government regulations and awareness campaigns, tobacco consumption remains high due to cultural acceptance, affordability, and accessibility of products like gutkha and khaini. This review examines the role of celebrity endorsements in tobacco cessation efforts, assessing their influence on public perception and behavior. Bollywood actors and sports icons, who hold immense cultural influence in India, have been leveraged in health campaigns to promote tobacco-free lifestyles. While some celebrity-driven initiatives have successfully raised awareness, surrogate marketing remains a critical challenge. Many celebrities indirectly endorse harmful products like pan masala and mouth fresheners, undermining tobacco control efforts. To counter this, stricter policies are needed to regulate celebrity endorsements, ensuring alignment with public health goals. This review highlights key strategies for maximizing the impact of celebrity-led health campaigns while minimizing the risks posed by surrogate marketing. By fostering sustained celebrity engagement and implementing robust policy measures, India can take significant steps toward reducing smokeless tobacco use and preventing oral cancer.